Intelligence from the perspective of inference. The problem of abduction for general artificial intelligence. - DUCA, Mihail (Annals of Philosophy, Social & Human Disciplines, 2023)
In this article, we want to analyze some of the limits of artificial intelligence. In order to have a significant development of this type of technology, one of the problems that requires a fundamental approach is the problem of inference. We will explore three types of inferences: deduction, induction, and abduction. Deduction was the basis for developing classical Artificial Intelligence (expert or symbolic system). Induction is used by modern Artificial Intelligence (neural networks), which requires a massive amount of data and very high computing powers. General Artificial Intelligence (currently in research) needs a theory of abduction that experts do not yet know how to program into a computational system.